PENGARUH KONSEP DIRI DAN KOMUNIKASI INTERPERSONAL TERHADAP INTERAKSI SOSIAL SISWA KELAS VIII DI SMP NEGERI 1 TIGO NAGARI - Irma Julita; M. Arif; Arjoni Arjoni; Sri Hartati (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
. The purpose of this study was to determine how much influence interpersonal communication and self-concept of class VIII students of SMP Negeri 1 Tigo Nagari have on students' social interactions. The research methodology used in this study is field research. The associative quantitative approach is used in this study. The number of students in the research group is 185 people. The sampling technique used in this study is the proportional random sampling technique, which is to divide the number of samples obtained per class by two. The total research sample is 126 samples. The research instrument is the result of the creation of scientists regarding social interaction, interpersonal communication, and self-concept surveys. To evaluate the research hypothesis, data analysis techniques such as simple linear regression and multiple linear regression are used. The results of this study indicate that: (1) with a percentage level of 43.2% and a significance value of 0.000 <0.05, self-concept (X1) has a positive and significant influence on social interaction (Y). (2) The interpersonal communication variable (X2) has a positive and significant influence on social interaction (Y), with a significance value of 0.000 <0.05